Working Interviews: Blending Fieldwork and Technical Work on Tour with Cirque du Soleil - Danson Faraday, Jacob (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2020)
For Cirque du Soleil’s touring arena show Corteo, music is a central feature of every performance. In this article, I focus on Corteo’s touring sound technicians, who play an essential role in the show’s musical presentation. I discuss a methodological approach to my ethnographic research, which provides new insights into large-scale intermedia performance environments like Corteo. I theorize a masculine-gendered, stoic mode of emotional labour that is enacted through voice-to-voice remote communication during performance. Through participant observation, public intercept interviews, and what I call “working interviews”—interviews with the sound technicians that take place during performances or other operational activities—I engage directly with the technical and emotional labour practices of musical production.